Pengembangan Smart Lighting Berbasis ESP32 dan Blynk untuk Mendukung Smart Village - Wahju Tjahjo Saputro; Hamid Muhammad Jumasa; Murhadi (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2026)
Efficient public lighting infrastructure plays a crucial role in supporting the development of smart villages. However, conventional street lighting systems are often energy-intensive and difficult to monitor and control remotely. This study aims to develop an Internet of Things (IoT)-based smart lighting system using the ESP32 WROOM microcontroller and the Blynk platform. The system was developed following the ADDIE framework, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The hardware components include an ESP32 WROOM DevKitC v4, a PZEM-004T v3 power monitoring module, a 2-channel optocoupler relay, and a smartphone. The software environment comprises Arduino IDE, Fritzing, EasyEDA, and Blynk as the user interface. Experimental results demonstrate that the proposed system can effectively monitor and control public lighting in real time through a smartphone from any location. The system exhibited fast response times, stable operation, and the potential to reduce electricity consumption by 23.33%. These findings indicate that the proposed solution effectively supports modern and energy-efficient smart village infrastructure while providing a low-cost, reliable, and easily deployable smart lighting model.